"Believe and tremble": A Note on Margaret Fuller's Roman Revolution - Matteson, John (Review of International American Studies, 2017)
John Matteson John Jay College of Criminal Justice City University of New York USA “Believe and tremble”: A Note on Margaret Fuller’s Roman Revolution Abstract: 1848, Europe’s year of revolutions, was also a revolutionary moment in the United States, for it witnessed the holding of the Seneca Falls Convention, the first formal gathering for the purpose of discussing the social and civil rights of women in America. A significant step on the road to Seneca Falls had taken place three years earlier when Margaret Fuller, the former editor of Emerson’s literary magazine The Dial, published Woman in the Nineteenth Century, an erudite and impassioned plea for female equality that had no precedent in American letters. Yet when the pioneering band of feminists gathered to ratify its Declaration of Sentiments at Seneca Falls, Fuller was thousands of miles away. The revolutionary movement to which she devoted her heart and toil that year was not the cause of American feminism, but the democratic revolution in Rome.